PENGUJIAN PERATURAN PERUNDANG-UNDANGAN MENURUT UNDANG-UNDANG DASAR 1945 - Jamri, Jamri; Muhsin, Muhsin (Selodang Mayang: Jurnal Ilmiah Badan Perencanaan Pembangunan Daerah Kabupaten Indragiri Hilir, 2023)
There are two legal regulation testing institutions in Indonesia that submit judicial reviews. First, to review laws against the 1945 Constitution, the authority to review them lies with the Constitutional Court. Second, testing through judicial review of statutory regulations under the law, if they conflict with the law, the authority lies with the Supreme Court. A study of legal regulations in Indonesia actually guarantees that every product of legal regulations, especially laws in Indonesia, in forming norms must not conflict with the norms contained in the constitution or the 1945 Constitution, as well as the formation of legislative regulations under the law must do not conflict with the law, where the 1945 Constitution itself has been placed in the highest position in statutory regulations. Pengujian peratuan perundang-undangan di indonesia terdapat dua lembaga untuk mengajukan judicial review. Pertama menguji UU terhadap UUD 1945 kewenangan mengujinya ada pada Mahkamah Konstitusi. Kedua pengujian melalui judicial review peraturan perundang-undangan dibawah undang undang apabila bertentangan dengan undang-undang kewenangannya berda di Mahkamah Agung. pengujian peraturan perundang-undangan di Indonesia tersebut sebenarnya mejaga agar setiap produk peraturan perundang-undangan khususnya Undang-Undang di Indonesia dalam pembentukan norma tidak boleh bertentangan dengan norma yang telah ada pada konstitusi atau UUD 1945, begitu juga dengan pembentukan peraturan perundang-undangan di bawah undang-undang tidak boleh bertentangan dengan undang-undang, dimana UUD 1945 sendiri telah di letakan pada posisi yang paling tinggi pada peraturan perundang-undangan.